Analysis of ums students' reception towards the meaning of self-confidence in somethinc x lifni sanders advertisement - Nugroho, Widya Mutiara; Saputro, Edy Purwo (Institute of Computer Science (IOCS), 2024)
This research aims to explore how students at Universitas Muhammadiyah Surakarta interpret and understand the message of self-confidence in the Somethinc X Lifni Sanders advertisement. Using a qualitative descriptive approach and Stuart Hall's encoding-decoding reception analysis model, this study focuses on how the advertisement's content, featuring models with diverse skin tones and hair types, conveys a message about inner beauty. Through in-depth interviews with students, this research seeks to comprehend how this message is received, understood, and translated by the young audience, and how it influences their perceptions of the concept of self-confidence. The findings of this study are expected to provide deeper insights into how advertisements can play a role in shaping and responding to views on beauty and self-confidence among today's youth